Purification of a lectin from Cratylia mollis crude extract seed by a single step PEG/phosphate aqueous two-phase system. Issue 7 (3rd August 2020) - Nascimento, Cynthia Oliveira; Pedrosa Brandão Costa, Romero Marcos; Soares, Paulo Antônio; Herculano, Polyanna Nunes; Porto, Tatiana Souza; Nascimento, Thiago Pajeú; Lima, Carolina de Albuquerque; Bezerra, Raquel Pedrosa; Teixeira, José Antônio; Coelho, Luana Cassandra Breitenbach Barroso; dos Santos Correia, Maria Tereza; Carneiro-da-Cunha, Maria das Graças; et al.
Abstract: The partitioning and purification of lectins from the crude extract of Cratylia mollis seeds (Cramoll 1, 4) was investigated in aqueous two-phase systems (ATPS). A factorial design model (2 4 ) was used to evaluate the influence of polyethylene glycol (PEG) molar mass (1500–8000 g/mol), PEG concentration (12.5–17.5% w/w), phosphate (10–15% w/w) concentration, and pH (6–8) on the differential partitioning, purification factor, and yield of the lectin. Polymer and salt concentration were the most important variables affecting partition of lectin and used to find optimum purification factor by experimental Box–Behnken design together with the response surface methodology (RSM). ATPS showed best conditions composed by 13.9% PEG1500, 15.3% phosphate buffer at pH 6, which ensured purification factor of 4.70. Sodium dodecyl sulfate–polyacrylamide gel electrophoresis showed a single band of protein with 26.1 kDa. Furthermore, results demonstrated a thermostable lectin presenting activity until 60 °C and lost hemagglutinating activity at 80 °C. According to the obtained data it can be inferred that the ATPS optimization using RSM approach can be applied for recovery and purification of lectins.